2014
DOI: 10.1177/0022427813520445
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Official and Self-report Records of Offending across Gender and Race/Ethnicity in a Longitudinal Study of Serious Youthful Offenders

Abstract: Objectives: Researchers have used both self-reports and official records to measure the prevalence and frequency of crime and delinquency. Few studies have compared longitudinally the validity of these two measures across gender and race/ethnicity in order to assess concordance. Methods: Using data from the Pathways to Desistance, a longitudinal study of 1,354 serious youthful offenders, we compare official records of arrest and self-reports of arrest over seven years. Results: Findings show moderate agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 46 publications
5
134
0
5
Order By: Relevance
“…Thus, the results may reflect both arrest prevalence as well as one's propensity to answer truthfully to questions regarding sensitive topics. Recall Piquero et al (2014) showed a moderate level of concordance between self-report and official records of arrest, suggesting there may be little difference between the prevalence rates reported here and the observed prevalence of arrest in official statistics. The second primary limitation was that respondents were young adults and, therefore, the findings may not generalize to middle or older adults.…”
Section: Arrest Prevalence By Race/ethnicitymentioning
confidence: 41%
See 1 more Smart Citation
“…Thus, the results may reflect both arrest prevalence as well as one's propensity to answer truthfully to questions regarding sensitive topics. Recall Piquero et al (2014) showed a moderate level of concordance between self-report and official records of arrest, suggesting there may be little difference between the prevalence rates reported here and the observed prevalence of arrest in official statistics. The second primary limitation was that respondents were young adults and, therefore, the findings may not generalize to middle or older adults.…”
Section: Arrest Prevalence By Race/ethnicitymentioning
confidence: 41%
“…Piquero, Schubert, and Brame (2014) used both self-reported arrests and official arrest records to examine correspondence between these two measures longitudinally within a sample of serious youthful offenders from the Pathways to Desistance study. The study found a moderate level of congruence between self-report measures and official records and that the agreement was stable over time.…”
mentioning
confidence: 99%
“…Previous studies suggest that this is a common phenomenon [40,95]. To more accurately capture desistance, we operationalize desistance using self-reported behavior for our qualitative analyses.…”
Section: Self-reported Desistancementioning
confidence: 99%
“…It is commonly accepted that there are three primary sources from which data are obtained to study delinquency and criminality: self-reports, officially recorded data, and victimization reports (Maxfield, Weiler, & Widom, 2000;Piquero, Schubert, & Brame, 2014; see also Weis, 1986 who also included direct observations and informant reports as data sources). Salient to the current project, research on arrests, whether self-reported or officially reported, relies heavily upon official data and/or data containing selfreported measures of arrest (Piquero et al, 2014;Pollock, Oliver, & Menard, 2014) because victimization studies, which are victim-based, do not lend themselves usefully to the study of arrest prevalence, which is offender-based (Weis, 1986).…”
mentioning
confidence: 99%
“…Salient to the current project, research on arrests, whether self-reported or officially reported, relies heavily upon official data and/or data containing selfreported measures of arrest (Piquero et al, 2014;Pollock, Oliver, & Menard, 2014) because victimization studies, which are victim-based, do not lend themselves usefully to the study of arrest prevalence, which is offender-based (Weis, 1986). The use of selfreport data is generally seen as an accepted method of measurement in the field of arrest research because of the findings of extensive research on the validity of self-report data as a measure of delinquency as mentioned above, but also because the use of self-report data in measuring arrest (as opposed to relying only upon officially-recorded arrests) is gaining traction (Hser, Anglin, & Chou, 1992;Maxfield et al, 2000;Piquero et al, 2014;Pollock, Menard, Elliott, & Huizinga, 2015).…”
mentioning
confidence: 99%